MULTI-ACTOR COLLABORATION IN THE DEVELOPMENT OF TAMAN BUKIT GELANGGANG AS A SUSTAINABLE TOURISM DESTINATION IN DUMAI CITY - Leny Marlini,; Khairul Rahman,; Dita Fisdian Adni, (Proceeding International Conference on Social Sciences, 2026)
This study aims to analyze the forms and processes of multi-actor collaboration in the development of Taman Bukit Gelanggang as a sustainable tourism destination in Dumai City. Multi-actor collaboration is considered an important strategy for realizing inclusive, participatory, and sustainable tourism development. This research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews with various stakeholders, including local MSME actors around the park, visitors, private sector representatives (PT KLK, PT Sinarmas, Semen Padang, Bank Riau, Hotel Grand Zuri), community leaders, regional financial analysts, and several local government agencies such as UPT Taman Bukit Gelanggang, the Department of Spatial Planning (Petaru), Bappeda, the Environmental Agency, and the Department of Youth, Sports, and Tourism of Dumai City. The data were further supported by field observations and document studies. The findings reveal that multi-actor collaboration in the development of Taman Bukit Gelanggang is still at an early stage, with several notable achievements, such as private sector participation in providing infrastructure support and government initiatives to develop the area as an urban green open space and tourism destination. However, the collaboration still faces several challenges, including weak institutional structures, leadership that has not fully fostered synergy among actors, suboptimal cross-sector communication, limited budget, and uneven community participation. This study highlights the importance of strengthening institutional design, fostering collaborative leadership, promoting open communication, and encouraging active participation from all actors to achieve sustainable management of Taman Bukit Gelanggang. Well directed and systematic collaboration will transform the park into not only a recreational space but also a center for social interaction, creative economy development, and environmental conservation in Dumai City.